Modern forms of processing and accessibility of resources in Graphic Collection Department - Bińkowska, Iwona (Biblioteka Uniwersytecka we Wrocławiu, 2015)
The article shows the applicability of photographic and digital technology to processing and access to information about the stock of Graphic Collection Department (GCD) alongside to a visual presentation of the collection in the form of images. Presented are both the oldest photocatalogs of prints taken from analog photos, as well as currently used digital files with metadata accessible by Digital Library of University of Wrocław and by Cultural Heritage portal. The paper also discusses the project of currently prepared hybrid catalog database which links functionality of digitized card catalogs of the Department with digital images of the cataloged objects, and offers an insight into the possibilities of the currently created and modified database which connects the functions of an inventory and a catalog. It also accentuates the participation of the Department employees in the subsequent stages of introducing modern technologies within the framework of projects, planned collections digitization, and in the interdepartmental activities carried out in Wrocław University Library.
Keywords: digital photography; Graphic Collection Department; repository; special collection inventories; iconographic document; photocatalog; special collections; digital library; special collection catalogs; iconographic source; analog photography; Wrocław University Library; digitization